Hubungan Toxic Parenting dan Duck Syndrome dengan Kesejahteraan Psikologis Remaja - Silva Daya; Dwi Sona; Yasintha Sari Pratiwi; Muhaimin Abdillah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the relationship between toxic parenting and duck syndrome with the psychological well-being of adolescents. This study uses a quantitative method with a correlational approach. The subjects of the study were grade X students of SMA Negeri 3 Samarinda who were selected using a purposive sampling technique with the criteria of male and female students, experiencing toxic parenting and duck syndrome with moderate to high categories, with a research sample of 92. The results of the study showed that toxic parenting and duck syndrome had a relationship with a sig. 0.000 <0.05 with a positive relationship direction which means that the higher the toxic parenting, the higher the tendency of duck syndrome in adolescents. In toxic parenting and psychological well-being there was a relationship with a sig. 0.001 <0.05 with a negative relationship direction which means that the higher the toxic parenting, the lower the psychological well-being. Furthermore, in duck syndrome and psychological well-being there was a relationship with a sig. 0.000 < 0.05, with a negative correlation, meaning that the higher the duck syndrome, the lower the psychological well-being. Finally, there was a correlation between toxic parenting and duck syndrome and psychological well-being, with a significant value of 0.000 < 0.05. Based on the research results, it can be concluded that toxic parenting and the tendency towards duck syndrome are simultaneously related to the psychological well-being of adolescents. Toxic parenting and duck syndrome are factors that need to be considered in efforts to improve the psychological well-being of adolescents, so parents and schools need to play a role in creating an environment that supports healthy psychological development.